2020
DOI: 10.1021/acs.molpharmaceut.9b01280
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Targeted Nanobody Functionalized Polymeric Micelles Loaded with mTHPC for Selective Photodynamic Therapy

Abstract: meta-Tetra(hydroxyphenyl)chlorin (mTHPC) is one of the most potent second-generation photosensitizers, clinically used for photodynamic therapy (PDT) of head and neck squamous cell carcinomas. However, improvements are still required concerning its present formulation (i.e., Foscan, a solution of mTHPC in ethanol/propylene glycol (40:60 w/w)), as mTHPC has the tendency to aggregate in aqueous media, e.g., biological fluids, and it has limited tumor specificity. In the present study, polymeric micelles with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 72 publications
3
42
1
Order By: Relevance
“…On the other hand, micelles from the corresponding benzyl-terminated polymer (entry 8, Table 1) showed substantially decreased size and size distribution (23 nm with PDI of 0.3, Figure 2A). This result is in accordance with our previous studies, in which it was demonstrated that micelles based on PCL 9 -PEG with a benzyl end group showed smaller size (17 nm), lower PDI (<0.1), and better stability than the non-benzylated polymer micelles [24,38]. Figure 2A shows that the different micelles based on P(CL/TMC-Bz)-PEG or P(TMC-Bz)-PEG block copolymers with different amounts of pendant benzyl groups (Entries 2-4, 6 and 7, Table 1) had small hydrodynamic diameters that slightly increased with the increasing chain length of the hydrophobic blocks (from 17-23 nm) with PDIs < 0.1 (Figure 2A).…”
Section: Preparation and Characterization Of Polymeric Micellessupporting
confidence: 93%
See 4 more Smart Citations
“…On the other hand, micelles from the corresponding benzyl-terminated polymer (entry 8, Table 1) showed substantially decreased size and size distribution (23 nm with PDI of 0.3, Figure 2A). This result is in accordance with our previous studies, in which it was demonstrated that micelles based on PCL 9 -PEG with a benzyl end group showed smaller size (17 nm), lower PDI (<0.1), and better stability than the non-benzylated polymer micelles [24,38]. Figure 2A shows that the different micelles based on P(CL/TMC-Bz)-PEG or P(TMC-Bz)-PEG block copolymers with different amounts of pendant benzyl groups (Entries 2-4, 6 and 7, Table 1) had small hydrodynamic diameters that slightly increased with the increasing chain length of the hydrophobic blocks (from 17-23 nm) with PDIs < 0.1 (Figure 2A).…”
Section: Preparation and Characterization Of Polymeric Micellessupporting
confidence: 93%
“…After the reaction (4 h at room temperature), the unreacted free thiols were blocked by reaction with maleimide (4 h at room temperature), and subsequently, the unreacted maleimide and unreacted Cy7 were removed by dialysis against THF/water (50:50 volume ratio) for 3 days. The successful coupling of Cy7 with the polymer and complete removal of free Cy7 was demonstrated by GPC analysis, with which the amount of Cy7 in the copolymer was quantified using UV-Vis detection at 755.5 nm, showing 17% coupling efficiency, as reported previously [38]. On average, one polymer chain carried 0.17 Cy7 label.…”
Section: Synthesis and Characterization Of Cy7-labeled P(cl/ttc)-pegsupporting
confidence: 59%
See 3 more Smart Citations